A review of epidemiological research on stroke and dementia and exposure to air pollution. Issue 7 (October 2018) - Béjot, Yannick; Reis, Jacques; Giroud, Maurice; Feigin, Valery
Background: Outdoor air pollution is now a well-known risk factor for morbidity and mortality, and is increasingly being identified as a major risk factor for stroke. Methods: A narrative literature review of the effects of short and long-term exposure to air pollution on stroke and dementia risk and cognitive functioning. Results: Ten papers on stroke and 17 on dementia were selected. Air pollution, and in particular small particulate matter, contributes to about one-third of the global stroke burden and about one-fifth of the global burden of dementia. It particularly affects vulnerable patients with other vascular risk factors or a prior history of stroke in low- and medium-income countries. New pathophysiological mechanisms of the cause-effect associations are suggested. Conclusion: Air pollution should be considered as a new modifiable cerebrovascular and neurodegenerative risk factor. This massive worldwide public health problem requires environmental health policies able to reduce air pollution and thus the stroke and dementia burden.